Exploring the Properties of Recycled Tyre Rubber for Flexible Asphalt Pavement - Nadia Khan; Asra Nafees; A. Hussain; G. Zaidi; M. Osama; S. Ghaffar (Journal of Basic & Applied Sciences, 2017)
In consideration of the issue related to the poor performance of asphalt pavements against climatic stresses and the need to contribute to the solution of the ever-increasing environmental hazards, the study paved the way for the recognition of using waste tyre as an asphalt binder modifier for pavement construction to settle the rising issue on waste disposal, while also improving the pavement properties. A series of experiments were conducted using different levels of recycled tyre rubber (RTR) substituted in asphalt binder. Marshall Stability and Marshall Immersion test were selected as basis to evaluate the properties. The results of experiments conducted on Marshall Mix samples demonstrated that stability of the pavements increased in a quadratic fashion with increasing fraction of RTR, and were found to be maximum at 10% rubber in asphalt mix, contributing an average enhancement of approximately 35% as compared to the conventional pavements. Furthermore, retained stability of samples was found to increase with increasing ratio of rubber substituted, making it a suitable candidate for modification in highly humid and rainy areas.